Pengaruh temperatur kalsinasi terhadap struktur mineral granit yang terdapat di Nagari Surian Kecamatan Pantai Cermin Kabupaten Solok (The effect of calcination temperature on the granite mineral structure in Nagari Surian, Pantai Cermin District, Solok Regency) - - Juliansyah; - Ratnawulan; Ahmad Fauzi (Department of Physics – Universitas Negeri Padang UNP, 2015)
Granite is an igneous rock in which the crystals have rough with the mineral composition of quartz, feldspar, plagioclase sodium and other minerals. It has done research on the granite from Surian by giving he at treatment for investigating the crystal structure of granite. The samples of granite were crushed and sieved till from powder and calcined at temperature 500 ℃ to 1000 ℃ for 1 hour. The results calcination were characterized by X-Ray Diffraction (XRD). The results calcination showed that the granite occurred alteration of structure on phase, such as from anorthic system with unit cell a = 8,256 Å, b = 12 842 Å and c = 14.088 Å to monoclinic structure with a = 8.1372 Å, b = 12.78 Å and c = 14.009 Å